The land of stories a grimm warning - Colfer, Chris (The land of stories, 2017)
The Brothers Grimm have a warning for the Land of Stories. Conner Bailey thought fairy tales were behind him, but now he finds himself on a mission to crack a two-hundred-year-old clue, left behind by the masters of storytelling. His twin sister, Alex, is training to become the next Fairy Godmother but her attempts at granting wishes never go as planned. Neither of them are expecting the coming battle, or the secret that will change their lives forever.